International relations and world politics - Viotti, Paul R. (Pearson, 2013)
Updated in its 5th edition, International Relations and World Politics is a toolkit that offers an authoritative survey of the field and practical ways to analyze current and future world problems. Drawn from the authors' experience as scholars and practitioners, this new edition was completely rewritten to focus on an enduring teaching and learning goal-how individuals can apply theory, history, geography, and more for a lifetime of understanding politics in a globalized world. Whether as actors themselves in world politics, participants in the global economy, or simply readers of world news, those reading International Relations and World Politics not only get more help to master the field's concepts but also get more help to understand that these are real-world ideas with real-world implications.